2001
DOI: 10.1046/j.1365-2362.2001.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid binding protein 2 and insulin resistance

Abstract: We demonstrated that the A54T polymorphism at the FABP2 locus is a risk factor for insulin resistance in a Caucasian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…The increased affinity of Thr-containing I-FABP for FA modifies intestinal fat absorption (14), postprandial lipid metabolism (13), and dyslipidemia (17,30). Although several investigators have reported an association between the Ala54Thr polymorphism and insulin sensitivity in adults (19,31,32), others have not demonstrated the influence of FABP2 gene variants on insulin levels and insulin resistance (16)(17)(18). Our data revealed no significant association between FABP2 polymorphism and fasting insulin.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The increased affinity of Thr-containing I-FABP for FA modifies intestinal fat absorption (14), postprandial lipid metabolism (13), and dyslipidemia (17,30). Although several investigators have reported an association between the Ala54Thr polymorphism and insulin sensitivity in adults (19,31,32), others have not demonstrated the influence of FABP2 gene variants on insulin levels and insulin resistance (16)(17)(18). Our data revealed no significant association between FABP2 polymorphism and fasting insulin.…”
Section: Discussioncontrasting
confidence: 66%
“…However, not all studies concur (16)(17)(18). In fact, the association between the FABP2 gene variants and lipid disorders appears to be much more complex than hypothesized, because the same I-FABP mutation had no similar impact on the composition of plasma lipids, the basal metabolic rate, or insulin, glucose, and lipid levels in different populations (19). Therefore, this issue requires more careful investigation, the findings of which may contribute toward better understanding of the specific role of I-FABP variants in exogenous fat transport and postprandial lipemic response.…”
mentioning
confidence: 98%
“…A greater fasting rate, but not postprandial fat oxidation rate, has also been reported in Korean men [33]. Additional studies, using various methods to assess insulin sensitivity, have similarly demonstrated lower insulin sensitivity in individuals with at least one copy of the Thr54 allele [34][35][36]. In one study, this decrease in insulin sensitivity was only evident while participants were consuming a high-fat meal [37].…”
Section: Discussionmentioning
confidence: 94%
“…This may be the reason for conflicting findings in different association studies: in some studies, associations have been shown between the A54T polymorphism and dyslipidemia [15][16][17]20], whereas in other studies this association has not been confirmed [22,43]. Similarly, contradictory associations have been shown with insulin plasma levels and with insulin sensitivity (association with insulin sensitivity: [10,19,40,41], no association: [13][14][15]22,43].…”
Section: Discussionmentioning
confidence: 97%
“…Chronically elevated free fatty acids result in an accumulation of intracellular fat in muscle and adipocytes and, consecutively, in insulin resistance, which is followed by hyperglycemia and type 2 diabetes mellitus [31,[37][38][39]. Thus, the association of the T54 coding variant with insulin resistance [10,19,40,41] may be explained by increased postprandial triglycerides and free fatty acids [16,36]. In the cohort examined, we were able to confirm that T54T homozygotes, when calculated irrespectively of promoter combination, have high postprandial triglyceride and low postprandial insulin sensitivity ( Fig.…”
Section: Discussionmentioning
confidence: 99%